Prognostic value of Fibrinogen/ Albumin in acute coronary syndrome patients with multiple coronary artery branch lesions - Tran, Quoc Bao; Doan, Chi Thang; Mai, Xuan Anh; Hoang, Anh Tien (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
ABSTRACT Acute coronary syndrome (ACS) comprises a pathophysiological spectrum of cardiovascular diseases related to atherosclerotic coronary plaque erosion. Oxidative stress and inflammation play pivotal roles in the development and progression of atherosclerosis, which affects circulatory proteins, including albumin and fibrinogen, thereby causing an imbalance in albumin-to-globulin and fibrinogen - to - albumin ratios. This study aimed to evaluate the characteristics and prognostic value of fibrinogen/albumin index (FAR) in ACS patients with multiple coronary artery branch lesions after 3 months follow-up. In this cross-sectional description and follow-up study, the major blood proteins in ACS patients were evaluated using standard methods. Out of 76 ACS patients, prognostic indicators such as hs - troponin T, pro - BNP, ejection fraction and GRACE scale were all much higher in high FAR group, the difference was significant (p < 0.05). More major cardiovascular events (MACE) occurred significantly in the high FAR group than in the low FAR group. ROC curve analysis showed that the FAR index can predict events occurring during the 3-month period after discharge from the ACS group (AUC = 0.681; p < 0.05), but the predictability was not high. During the follow-up of MACE, the Kaplan-Meier analysis showed that patients with FAR > 10.3 had a higher risk of MACE than the FAR ≤ 10.3 (p < 0.05). Overall, FAR could be used as a routine prognostic factor in ACS with multiple coronary artery branch lesions with percutaneous coronary artery intervention.